Ethnic disparities of poor households by a multilevel analysis of household and contextual effects: Evidence from a multi-ethnic county of China. - Junfeng Tian; Binyan Wang; Li Ma; Yunyan Li; Shijun Wang (PLoS ONE)
Poverty in multi-ethnic regions has always been a concern due to its complex factors and persistent nature. Using a sample of 8,482 ethnic majority-headed households and 2,011 ethnic minority-headed households distributed in 200 villages of Wangqing County, China, this study uses hierarchical linear models to examine the factors of income at the household level, the ethnic disparities of the household-level effect, and the contextual effect on household-level outcomes. The findings suggest that, in comparison to the majority group, there exists a smaller income gap between male-headed and female-headed poor households within the minority group. Moreover, the positive impact of participating in off-farm work and receiving welfare payments on the income of poor households is significantly stronger within the minority group. These results not only highlight ethnic disparities in household-level effects but also underscore potential influences of ethnicity on the income dynamics of poor households. The contextual effect demonstrates that modifying the environment of poor households can either enhance or diminish some of the impacts resulting from factors at the household level, thereby facilitating the formulation of more effective targeting strategies at different levels. This study provides an important reference for understanding the ethnic differences of poor households and the mechanism of their income from a multilevel perspective.